Fragile X Syndrome as an interneuronopathy: a lesson for future studies and treatments - Tempio, Alessandra; Boulksibat, Asma; Bardoni, Barbara; Delhaye, Sébastien (Frontiers in Neuroscience, 2023)
Fragile X Syndrome (FXS) is the most common form of inherited intellectual disability (ID) and a primary genetic cause of autism spectrum disorder (ASD). FXS arises from the silencing of the FMR1 gene causing the lack of translation of its encoded protein, the Fragile X Messenger RibonucleoProtein (FMRP), an RNA-binding protein involved in translational control and in RNA transport along dendrites. Although a large effort during the last 20 years has been made to investigate the cellular roles of FMRP, no effective and specific therapeutic intervention is available to treat FXS. Many studies revealed a role for FMRP in shaping sensory circuits during developmental critical periods to affect proper neurodevelopment. Dendritic spine stability, branching and density abnormalities are part of the developmental delay observed in various FXS brain areas. In particular, cortical neuronal networks in FXS are hyper-responsive and hyperexcitable, making these circuits highly synchronous. Overall, these data suggest that the excitatory/inhibitory (E/I) balance in FXS neuronal circuitry is altered. However, not much is known about how interneuron populations contribute to the unbalanced E/I ratio in FXS even if their abnormal functioning has an impact on the behavioral deficits of patients and animal models affected by neurodevelopmental disorders. We revise here the key literature concerning the role of interneurons in FXS not only with the purpose to better understand the pathophysiology of this disorder, but also to explore new possible therapeutic applications to treat FXS and other forms of ASD or ID. Indeed, for instance, the re-introduction of functional interneurons in the diseased brains has been proposed as a promising therapeutic approach for neurological and psychiatric disorders.